Emergency Department Crowding: Time for Interventions and Policy Evaluations. (7th February 2012) - Boyle, Adrian; Beniuk, Kathleen; Higginson, Ian; Atkinson, Paul
Abstract : This paper summarises the consequences of emergency department crowding. It provides a comparison of the scales used to measure emergency department crowding. We discuss the multiple causes of crowding and present an up-to-date literature review of the interventions that reduce the adverse consequences of crowding. We consider interventions at the level of an individual hospital and a policy level.